Система поддержки принятия решений по повышению эффективности гидроаэродинамических процессов во вспомогательных элементах энергетических агрегатов - Арсирий, Е.А.; Антощук, С.Г.; Арсирий, В.А.; Гуда, А.И. (Управляющие системы и машины, 2015)
Разработана распределенная проблемно-ориентированная система поддержки принятия решений, основанная на соответствующих информационных технологиях при проведении комплексных мониторинга и моделирования состояния гидроаэродинамических процессов в энергетических агрегатах, их вспомогательных элементах и комплексной аналитико-визуальной обработке данных физического моделирования гидроаэродинамических процессов в прототипах вспомогательных элементов энергетических агрегатов. Система позволяет решить важную научно-прикладную проблему повышения эффективности гидроаэродинамических процессов во вспомогательных элементах энергетических агрегатов. Розроблено розподілену проблемно-орієнтовану систему підтримки прийняття рішень, яка базується на відповідних інформаційних технологіях при проведенні комплексних моніторингу та моделюванні стану гідроаеродинамічних процесів в енергетичних агрегатах і їх допоміжних елементах, а також комплексної аналітико-візуальної обробки даних фізичного моделювання гідроаеродинамічних процесів в прототипах допоміжних елементів енергетичних агрегатів. Система дозволяє вирішити важливу науково-прикладну проблему підвищення ефективності гідроаеродинамічних процесів у допоміжних елементах енергетичних агрегатів. The distributed problem-oriented system is developed to support the decision making on increasing efficiency of the hydroaerodynamic processes (HP) inside the minor elements power units. This system is based on three brand new informational technologies to support the decision making connected to each other. These technologies are intended to conduct: – complex monitoring HP in combined conceptual objects power equipment at a basic level – power units based on the analysis of the regulatory-referential design and operational information about power units; – complex modeling HP in simple conceptual objects power equipment at a basic level – the minor elements based on the analysis of the regulatory-referential design and operational information as well as information retrieved from a physical modeling; – complex analytic and visual processing data from a physical modeling HP inside the minor element prototypes of the power units to synthesis of their updated physical prototype. System support decision making is functional-distributed and consists of subsystems on input, storage, data analysis and decision making, combined by interface tools for decision making person. Informational relationship of mentioned functionaldistributed subsystems is based on decision making person interface and developed digital mockup of the power equipment. The digital mockup is a part of united informational space of energetic enterprise and joins the following equipment features: the technological – data gathering servers, geometric and tech-economic – ASU servers and hydrodynamic – modeling servers. Thus, the developed system gives the opportunity to automate decision making process on increasing efficiency HP in power equipment at a basic level, where the major idea is to provide decision making person complete information about HP state inside the power units and its minor elements and developing rational scenarios of the organizational and production control over the reconstruction.